A preliminary study of the effects of aircraft noise on families who reside in close proximity to an airport - D. Pillay; K. Archary; S. Panday (South African Family Practice)
Background: The use of air transportation has grown in the last century, escalating the noise exposure of families residing in close proximity to airports. The audiological effects need to be assessed to determine the impact of this increase on children and young adults living near to airports in South Africa.